INDUSTRIALIZACION, BURGUESIA Y CLASE OBRERA EN MEXICO: EL CASO DE MONTERREY - Vellinga, Menno (1981)
TRADUCCION DE: ECONOMIC DEVELOPMENT AND THE DYNAMICS OF CLASS: INDUSTRIALIZATION, POWER AND CONTROL IN MONTERREY, MEXICO